Implementasi Program Urban Farming Sebagai Strategi Pembangunan Ketahanan Pangan Perkotaan (Studi Di Kelurahan Made, Kecamatan Sambikerep, Kota Surabaya) - Mima Kurniasih (Jurnal Administrasi Publik, 2015)
Abstack: Implementation of Urban Farming Program as Strategy of Urban Food Security Development (Study at Kelurahan Made, Kecamatan Sambikerep, Kota Surabaya) Urban Farming program is one step that has been taken to improve food security for the poor community. In regarding to the availability of land and the increased demand for food due to population growth, one reasonable step to take is using the narrow land, such as backyard and rice field, for productive farming activities. The purpose of study is to describe andÂ  analyse implementation of Urban Farming program. Also, to provide contribution in improving food security in household. Research type is descriptive with qualitative approach. The focus of research is given upon the research boundary suggested by David C. Korten, Wahab and Edward III. A main instrument of data collection technique is data triangulation. Data are then analyzed with Miles, Huberman and Saldanaâ€™s data analysis model. Result of research indicates that the implementation of Urban Farming Program has been successful. The presence of Urban Farming Program can improve food security of the poor community, and it is indicated by the improvement of food stock and the relief for food expense. The program still needs improvement, especially related to stakeholder participation. Keywords: program implementation, Urban Farming program, food security Abstrak: Implementasi Program Urban Farming sebagai Strategi Pembangunan Ketahanan Pangan Perkotaan (Studi di Kelurahan Made, Kecamatan Sambikerep, Kota Surabaya) Program Urban Farming merupakan salah satu langkah yang ditempuh untuk meningkatkan ketahanan pangan bagi masyarakat miskin. Dengan ketersediaan lahan dan semakin meningkatnya kebutuhan pangan karena peningkatan jumlah penduduk, salah satu langkah yang ditempuh adalah dengan memanfaatkan lahan sempit seperti pekarangan dan lahan sawah yang tersisa untuk kegiatan pertanian. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis implementasi program Urban Farming, kontribusinya dalam meningkatkan ketahanan pangan di tingkat rumah tangga. Penelitian yang digunakan adalah deskriptif kualitatif. Fokus diperoleh dari pendapat Korten, Wahab, dan Edward III, dengan teknik pengumpulan data dengan triangulasi. Sedangkan data yang diperoleh dianalisa menggunakan model analisa data Miles, Huberman dan Saldana. Hasil penelitian menunjukkan implementasi program cukup berhasil. Namun, perbaikan ketahanan pangan dapat diamati dari perbaikan ketersediaan dan pengurangan beban untuk pengeluaran pangan ditingkat rumah tangga miskin. Sedangkan masih dibutuhkan perbaikan program, terutama pada keterlibatan stakeholder.